Detection of gonadotropin-releasing hormone and somatostatin-14 containing cells in the mammary gland of guinea pigs - Tarakci, Berrin Gencer; Yaman, Mine; Bayrakdar, Ali (My University, 2007)
The existence of numerous neuropeptides in milk is well established. It is still unclear whether these neuropeptides are produced by the mammary gland or that the gland concentrates them from the general circulation. The aim of the study was to examine the possible localization of these neuropeptides in the mammary gland of guinea pigs at different physiological states by immunohistochemistry. Specific primers have been used for the somatostatin, vasoactive intestinal polypeptide, neurotensin, cholecystocinin, oxytocin, gonadotropin-releasing hormone and growth hormone. Among all the neuropeptides that have been examined gonadotropin-releasing hormone and somatostatin immunoreactivity were found in the mammary gland of lactating guinea pigs, but not in virgin and pregnant guinea pigs. Immunoreactivity was observed in the epithelial cells that compose the secretory alveoli and in the secretory material.
Keywords: Guinea pig; Mammary gland; Neuropeptides